A model of essential factors for e-government crowdsourcing initiatives - Cupido, Kevin (Department of Information Systems, 2016)
Crowdsourcing using web technologies accesses the potential of a large network of people who respond to an 'open call'. Successful commercial implementations of crowdsourcing have succeeded in mobilising a large number of participants and leveraging these 'crowds' as a source of ideas, and for problem solving (Geiger et al., 2011, Howe, 2006). While governments perceive citizens as being apathetic when it comes to political participation, the citizen perspective is that their participation is "spectator politics where ordinary people have mostly become endorcees of pre-designed planning programmes" (Williams, 2006, p. 197). Part of the reason for the lack of participation could be due to the increasing complexity of governing and the absence of alternative, more inclusive methods of participation. Brabham (2009) has advocated for the use of crowdsourcing in the public sector as a possible means of increasing public participation, and for governments to access citizens as a source of ideas and solutions. However within e-Government there is a lack of knowledge regarding the implementation of crowdsourcing platforms (Koch & Brunswicker, 2011). The main research questions addressed in this study is: Which crowdsourcing factors are applicable and appropriate for government crowdsourcing implementations, so that citizens would be motivated to participate in such initiatives? As crowdsourcing lacks a theoretical and conceptual foundation (Pedersen et al., 2013, Geiger et al., 2011) a conceptual model for government crowdsourcing implementations is developed and tested. The model uses Self-Determination Theory (SDT) to examine citizen motivation and the influence of incentives or rewards on participation. The model also addresses system factors such as task clarity and types, management, and feedback. The model also includes effort, performance expectancy, as well as behavioural intention from Unified Theory of Acceptance and Use of Technology (UTAUT).